Clinical features of patients with Yin Yang 1 deficiency causing Gabriele‐de Vries syndrome: A new case and review of the literature. (3rd November 2021) - Khamirani, Hossein Jafari; Zoghi, Sina; Namdar, Zahra Mehdipour; Kamal, Neda; Dianatpour, Mehdi; Tabei, Seyed Mohammad Bagher; Mohammadi, Sanaz; Dehghanian, Fatemeh; Farbod, Zahra; Dastgheib, Seyed Alireza
Abstract: Background : Gabriele‐de Vries syndrome is a rare autosomal dominant genetic disease caused by de novo pathogenic variants in YY1 . In this study, we report a 10‐year‐old boy with a de novo novel pathogenic variant in YY1, the first Iranian patient with Gabriele‐de Vries Syndrome. Methods : The novel de novo pathogenic variant detected in this study (NM_003403:c.690delA, p.Glu231Ilefs*25) was identified by whole‐exome sequencing and confirmed by Sanger sequencing. Results : The proband presented with delayed motor and speech development, ataxia, abnormal gait, autistic behavior, brain atrophy, and severe learning disability. Finally, we provide a case‐based review of the clinical features associated with Gabriele‐de Vries Syndrome. Thus far, merely 13 Gabriele‐de Vries Syndrome patients have been reported in the literature. Conclusion : The investigations for a suspected case of Gabriele‐de Vries Syndrome must involve molecular diagnosis of the disease and its underlying genetic defect because the clinical investigations are generally variable and nonspecific.